Case Report of a Presumed Stonefish (Synanceia sp.) Envenomation and Successful Treatment with Antivenom - Baso, Shannon; Little, Mark (Journal of Current Toxicology and Venomics, 2025)
IntroductionStonefish envenoming occurs when a person comes in contact with the fish’s dorsal spines. This results in immediate and severe pain, with some reports of necrosis and limb swelling, and rare reports of death. While management focuses on pain management, an antivenom is available with a number of reports of improving pain. However, the evidence of the effectiveness of antivenom is based on case reports and animal work. A recent case series from Australia reported five cases where stonefish antivenom did not relieve pain and further analgesia was required. There are differing opinions in Australia on whether stonefish antivenom should be used in the management of stonefish envenoming.Case ReportTwo patients, aged 40 and 50 years, were stung on a finger when putting their hands into water in northern Australia. Both of them felt immediate and severe pain, and developed cyanosed fingers. Both of the patients received 20 mg intravenous morphine and hot water first aid, but remained in severe pain. Both of them also received 1 ampoule (2000 U) of Sequirus stonefish antivenom, and within 1 hour of the antivenom commencement, the pain was gone, and digit discolouration had markedly improved. There was no adverse reaction of the antivenom observed, and both the patients were pain-free with normal fingers at follow-up weeks later.ConclusionWe have, herein, reported two cases of presumed stonefish sting where early administration of intravenous stonefish antivenom has appeared to resolve the severe pain and resulted in a marked improvement in digit discolouration. Further work is required to better understand the stonefish venom and how effective stonefish antivenom is in the treatment of stonefish envenoming.
Keywords: antivenom